Dynamic model and CPG network generation of the underwater self-reconfigurable robot. (17th July 2016) - Yang, Ke
Abstract: In this paper, we use one unified method based on graph theory and path matrix to solve problems of kinematic and dynamic modeling and Central Pattern Generator (CPG) network generation of different configurations of the underwater self-reconfigurable robot. Considering complex and changeable characteristics of the underwater self-reconfigurable robot, we introduce the knowledge of graph theory to solve the problem of the unified configuration description and use a path matrix to describe different configurations. Combining Kane's equations, we propose a unified modeling method of the underwater self-reconfigurable robot. In view of rhythmic movement characteristics of the underwater self-reconfigurable robot, we introduce CPG as the basic unit. Combining the path matrix, the method of making the CPG network evolving from the configuration is proposed. Taking typical configurations of the underwater self-reconfigurable robot as example, applicability and effectiveness of the proposed method are verified. Abstract :